Psychotropic medication use among postgraduate students and associated factors - Nayara Paula Fernandes Martins Molina; Assis do Carmo Pereira Junior; Gabriela Di Donato; Leonardo Bigolin Jantsch; Riccardo Lacchini; Adriana Inocenti Miasso (Bioscience Journal)
This study examined the prevalence and influencing factors of psychotropic medication use among 5,334 postgraduate students from across Brazil. It was a crosssectional and observational investigation, which collected electronic data through the REDCap platform over three months in 2022. The data analysis revealed several factors associated with psychotropic medication use, including psychological distress in the previous year, self-reported mental disorders, continuous medication use, pandemic related disruptions, a positive COVID-19 test, and illicit drug use during the pandemic. However, certain factors, such as living in the north or southeast regions and accessing psychological counseling before the pandemic, showed a protective association. These findings demonstrate that mental health policies that support and monitor students using psychotropic medications are crucial for enhancing well-being in postgraduate programs.